2016
DOI: 10.1016/j.jaci.2016.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of T H cytokine profiles in patients with chronic rhinosinusitis: A multicenter study in Europe, Asia, and Oceania

Abstract: T cytokine levels, eosinophilic/neutrophilic patterns, and SE-specific IgE expressions show extreme diversity among patients with CRS from Europe, Asia, and Oceania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
551
5
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(578 citation statements)
references
References 31 publications
15
551
5
7
Order By: Relevance
“…In contrast, CRSsNP has more diverse immunological endotypes that remain poorly defined. 83 In CRSwNP, eosinophilic inflammation is present with amplification of IL-4-, IL-5-and IL-13-driven pathways. Recent work has highlighted type II ILC-infiltrated polyp tissue with Th2-skewed cells expressing IL-25R and IL-33R.…”
Section: Ch Ronic R Hin Osin Usitis and Sinon Asal Remodellingmentioning
confidence: 99%
“…In contrast, CRSsNP has more diverse immunological endotypes that remain poorly defined. 83 In CRSwNP, eosinophilic inflammation is present with amplification of IL-4-, IL-5-and IL-13-driven pathways. Recent work has highlighted type II ILC-infiltrated polyp tissue with Th2-skewed cells expressing IL-25R and IL-33R.…”
Section: Ch Ronic R Hin Osin Usitis and Sinon Asal Remodellingmentioning
confidence: 99%
“…In Western populations, CRSwNP is near uniformly an eosinophilic condition, whereas CRSsNP is more heterogeneous. 4,5 In the United States, there currently are no data on the relative frequency of endoscopic sinus surgeries (ESS) performed for CRSwNP versus CRSsNP. Previous studies on CRSwNP demonstrate increased rates of revision surgery but also greater improvements after sinus surgery compared with patients with CRSsNP.…”
Section: Hronic Rhinosinusitis (Crs) Is Characterized By Mucosal Inmentioning
confidence: 99%
“…Discrepancies between the studies could be due to different sampling methods or different presentations of the disease; studies found significant variation in cytokine profiles between different countries of origin or ethnicities in CRS. 55 Therefore, similar to AR, additional investigation is needed, focused more specifically on Treg function and less on expression of markers to determine their presence or absence.…”
Section: Alterations In Treg Numbers and Functions In Ar And Crswnpmentioning
confidence: 99%